Learning and growth perspective: Banking sectors evidence - Atefa Sonya Memon; Nazish Baladi (Jurnal Inovasi Ekonomi, 2020)
This study aims to measure learning and growth on employee performance through the Balanced Scorecard (BSC). The study has incorporated a quantitative research design that the research questionnaire adapted and modified based on the five Likert scale responses from 1 as strongly disagree to 5 as strongly agree. The primary data collection has been compiled for Habib Bank Limited and Allied Bank Limited in Hyderabad. The probability sampling has been used to conduct the study with a sample size of 40 employees selected for the study. The entire analysis of this research is carried out through analysis of variance (ANOVA) by SPSS. The result concluded that there is a significant difference in the mean values of different variables such as awareness, encourages employee accuracy, and enhances employee accountability. In contrast, other variables have no significant differences. The attentive focus on accountability, accuracy, and awareness of employees will improve employees' performance effectively. The targeted banks should explore the BSC for implementation to improve employee performance.